2002
DOI: 10.1093/jn/132.6.1107
|View full text |Cite
|
Sign up to set email alerts
|

Oral Chromium Picolinate Improves Carbohydrate and Lipid Metabolism and Enhances Skeletal Muscle Glut-4 Translocation in Obese, Hyperinsulinemic (JCR-LA Corpulent) Rats

Abstract: Human studies suggest that chromium picolinate (CrPic) decreases insulin levels and improves glucose disposal in obese and type 2 diabetic populations. To evaluate whether CrPic may aid in treatment of the insulin resistance syndrome, we assessed its effects in JCR:LA-corpulent rats, a model of this syndrome. Male lean and obese hyperinsulinemic rats were randomly assigned to receive oral CrPic [80 microg/(kg. d); n = 5 or 6, respectively) in water or to control conditions (water, n = 5). After 3 mo, a 120-min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

19
109
2
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(132 citation statements)
references
References 57 publications
19
109
2
2
Order By: Relevance
“…Cr is an essential element required for normal carbohydrate and lipid metabolism. Many scientists have demonstrated that a severe deficiency in Cr led to fasting hyperglycemia, glucosuria and impaired growth [42]. Our results are in good agreement with other investigation, which reported that the administration of Cr has a beneficial role on diabetes mellitus patients [43,44].…”
Section: Discussionsupporting
confidence: 92%
“…Cr is an essential element required for normal carbohydrate and lipid metabolism. Many scientists have demonstrated that a severe deficiency in Cr led to fasting hyperglycemia, glucosuria and impaired growth [42]. Our results are in good agreement with other investigation, which reported that the administration of Cr has a beneficial role on diabetes mellitus patients [43,44].…”
Section: Discussionsupporting
confidence: 92%
“…Cr is an essential element required for normal carbohydrate and lipid metabolism. Many scientists have demonstrated that a sever Cr deficiency led to fasting -hyperglycemia, glucosuria and impaired growth [52]. Our older patients had lower values of Cr in scalp hair samples which is consistent with other studies [53], where age-related decreases of Cr in hair as compared to matched normal subjects were described.…”
Section: Discussionsupporting
confidence: 92%
“…We have reported previously that the insulin resistance of the cp/cp rat is accompanied by enhanced serine kinase activity and attenuated IRS-1 phosphorylation and phosphatidylinositol-3 kinase activity following insulin stimulation [40,41]. The abnormal signal transduction may well extend to other pathways that are related and that can be upregulated by arginine or NO through as yet unknown mechanisms.…”
Section: Discussionmentioning
confidence: 96%